2018
DOI: 10.1080/17461391.2018.1554707
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanical characteristics of high‐performance endurance running

Abstract: The biomechanical profile of high-level endurance runners may represent a useful model that could be used for developing training programmes designed to improve running style. This study therefore sought to compare the biomechanical characteristics of high-performance and recreational runners. Kinematic and kinetic measurements were taken during overground running from a cohort of 14 highperformance (8 male) and 14 recreational (8 male) runners, at four speeds ranging from 3.3 to 5.6 ms-1. Two-way ANOVA analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 35 publications
3
31
0
1
Order By: Relevance
“…Further, these results suggest that a distal-to-proximal shift in positive joint kinetics exists in low compared to high volume runners as a result of lesser power generation at the ankle. Although angular power and work were not reported, Preece et al 27 observed larger peak plantarflexor torque in young runners with higher weekly volume (~87 km) compared to those with lower weekly volume (~43 km) suggesting some influence of volume in young runners. In the current study, despite not reaching significance (P = .081), a closer look at the age by volume group interaction effect for peak plantarflexor torque demonstrates a larger peak torque in high compared to low volume young runners only (d = 0.73, Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…Further, these results suggest that a distal-to-proximal shift in positive joint kinetics exists in low compared to high volume runners as a result of lesser power generation at the ankle. Although angular power and work were not reported, Preece et al 27 observed larger peak plantarflexor torque in young runners with higher weekly volume (~87 km) compared to those with lower weekly volume (~43 km) suggesting some influence of volume in young runners. In the current study, despite not reaching significance (P = .081), a closer look at the age by volume group interaction effect for peak plantarflexor torque demonstrates a larger peak torque in high compared to low volume young runners only (d = 0.73, Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…Ground reaction forces are relevant parameters for running analysis (Pohl et al, 2009;Crowell and Davis, 2011;Van Der Worp et al, 2016;Clark et al, 2017). They partially describe the center of mass' state of motion during running and are often used by sport scientists and clinicians to analyze the mechanical risk-factors of running related injuries (Bredeweg et al, 2013;Napier et al, 2018) and/or athletic performance (Preece et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recreational and high-caliber club runners have been analyzed during good-standard races of varying distance; footstrike patterns have also been reported for laboratory testing using treadmills (Hanley and Tucker, 2018;Kubo et al, 2015) and an indoor runway (Preece et al, 2018). However, no previous research has analyzed the footstrike patterns of world-class marathon runners, or the changes that occur, as they complete a World Championship race.…”
Section: Introductionmentioning
confidence: 99%